2021
DOI: 10.1111/jfpp.15247
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds, antioxidant activity, and color retention of beetroot ( Beta vulgaris L.) powder: Effect of steam blanching with refrigeration and storage

Abstract: Beetroot (Beta vulgaris L.) was subjected to different blanching treatments, that is, T1 (hot-water blanching with cold water immersion), T2 (steam blanching with cold water immersion) and T3 (steam blanching with refrigeration) for obtaining beetroot powder. Fourier transform infrared spectroscopy was used for the evaluation of functional groups in the different blanching treatments. Fresh beetroot and the sample with maximum functional groups, that is, T3 was further used to analyze chemical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
11
2
Order By: Relevance
“…The results showed that the beetroots prepared by different drying methods varied from 15.82±0.15 to 24.71±0.47 mg RE/g, which were significantly lower than the range proposed by Hamid and Nour [45] of sun-dried, oven-dried and freezedried beetroots with the values of 34.74±0.54, 33.28±0.72 and 36.11±0.95 mg RE/g, respectively. The greatest total flavonoids content was observed in HPD beetroots, which can be explained by the fact that the thermal treatment of beetroots resulted in the acceleration of the release of bound flavonoid compounds because of the breaking down of the cellular constituents, as well as the inactivation of endogenous oxidative enzymes increased the flavonoid content in the beetroots [5]. There are so many kinds of bioactive compounds in beetroots, two bioactive compounds (betalain and total flavonoids) were considered in this study.…”
Section: Discussion Of the Results Of The Study Of Quality Attributes...mentioning
confidence: 97%
See 1 more Smart Citation
“…The results showed that the beetroots prepared by different drying methods varied from 15.82±0.15 to 24.71±0.47 mg RE/g, which were significantly lower than the range proposed by Hamid and Nour [45] of sun-dried, oven-dried and freezedried beetroots with the values of 34.74±0.54, 33.28±0.72 and 36.11±0.95 mg RE/g, respectively. The greatest total flavonoids content was observed in HPD beetroots, which can be explained by the fact that the thermal treatment of beetroots resulted in the acceleration of the release of bound flavonoid compounds because of the breaking down of the cellular constituents, as well as the inactivation of endogenous oxidative enzymes increased the flavonoid content in the beetroots [5]. There are so many kinds of bioactive compounds in beetroots, two bioactive compounds (betalain and total flavonoids) were considered in this study.…”
Section: Discussion Of the Results Of The Study Of Quality Attributes...mentioning
confidence: 97%
“…The average beetroot composition is water (88 %), carbohydrate (9.56 g/100 g), sugar (6.76 g/100 g), protein (1.16 g/100 g), fiber (2.80 g/100 g), fat (0.17 g/100 g), vitamin C (4.90 mg/100 g), and phytosterols (25.00 mg/100 g) [3].Statistics showed that the annual production of beetroots reached 307 million tons in 2017 [4]. Beetroot is consumed in raw and cooked form, and is rich in betalains pigment, which has been approved as a natural colorant E-162 by the European Union [5]. The betalains can be used in dry mixes, sweets, jam, and jellies, but are sensitive to various environmental and technological process conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…There were significant differences in total flavonoids content among different microwave-assisted drying methods (p<0.05). Beetroots prepared by VD+LMD and HAD+LMD showed relatively high total flavonoids content, which can be explained by the fact that the thermal treatment of beetroots resulted in the acceleration of the release of bound flavonoids, due to the breaking down of the cellular constituents, as well as the inactivation of endogenous oxidative enzymes, increased the total flavonoids content in beetroots [5]. There are many kinds of bioactive compounds in dried beetroots.…”
Section: Discussion Of the Results Of Studying The Influence Of Diffe...mentioning
confidence: 99%
“…Beetroot is considered as a health-promoting food because it contains bioactive compounds for health promotion, such as betalains, phenolics, vitamins, minerals, carotenoids, nitrate, flavonoids, saponins, ascorbic acids, glycine, betaine and folate [4]. Beetroot is rich in betalain pigment, which has been approved as a natural colorant E-162 by European Union [5]. Betalains are commonly used for coloring a variety of foods, such as sauces, jam, jellies, ice cream, desserts, yogurt, candies and breakfast cereals.…”
Section: Introductionmentioning
confidence: 99%
“…Kaur et al [15] stored red beet powder in HDPE bags at 4°C for 3 months, and betacyanin, betaxanthin and betalain analyses were performed during storage. They stated that there was a loss of 21.03, 17.95 and 21.13% in the betacyanin, betaxanthin and betalain contents of samples, respectively.…”
Section: Effect Of Storage Conditions On Betanin Content Of Freeze-dr...mentioning
confidence: 99%